How Urban Land Titling and Registry Reform Affect Land and Credit Markets : Evidence from Lesotho - Deininger, Klaus; Ali, Daniel Ayalew (World Bank, Washington, DC, 2022)
Using spatial fixed effects and time-varying controls, this paper draws on complete registry data for 1981–2019, supplemented by satellite imagery, to analyze impacts of urban land titling for some 40,000 grid cells in Lesotho. Beyond confirming the short-term impacts on female co-ownership and investment, previously reported, the paper documents medium-term impacts on land sale and mortgage market activity and women’s participation in these markets. Although titling was instrumental in ensuring the effectiveness of an earlier legal reform that allowed women to be co-owners of land, the credit and land market effects are due not to titling but to changes in policy to reduce the transaction cost of registering land that took effect just before titling started. Downward shifts in the time required to register transactions support this interpretation. The paper concludes by discussing what the evidence implies for design and evaluation of property registration programs.